Technologies for developing inclusive competence of future defectologists - Sattorova Mokhira Aminkulovna, (THE INNOVATION ECONOMY, 2026)
in this article, the modern stage of reforming general secondary education in our country is closely related to the changes carried out in the social and economic spheres, aimed at achieving greater independence in the selection of a strategic vector for the preparation of future defectologists for inclusive education, both for an edu cational institution and for a teacher - for the purpose of continuous professional development. The need for the development of educational technologies for the continuous professional development of future defectologists, the development of technology for improving the essence and content of educational technologies in their activities outside the audience, the preparation of future defectologists for inclusive education is presented.Professional dif ficulties in the education and upbringing of children with developmental disabilities are a number of social and pro fessional-pedagogical factors, it is thought about the need to create special conditions that ensure the adaptation of special educational needs in accordance with their nature. The results of modern research describe the issues of providing education and training to persons with disabilities, creating opportunities for them, forming a new know ledge base in the field of Personnel Training and pressing the problem of the search for tools for their development by future teachers.